DESKRIPSI RENCANA PELAKSANAAN PEMBELAJARAN TEMATIK GURU KELAS IV SEKOLAH DASAR - Katrina Katrina; Kartono Kartono; Asmayani Asmayani (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe the thematic learning implementation plan based onthe regulations on education and culture number 22 of 2016 concerning thestandard of the primary and secondary education process. The research methodused is descriptive method with qualitative research forms. The data source ofthis research is the fourth grade teacher of elementary school 06 PontianakSelatan. The data researched was in the form of a thematic learningimplementation plan document and the results of the interview for thepreparation of the learning implementation plan for the fourth grade teachers inElementary School 06 South Pontianak. The results show that the preparationand components of the learning implementation plan made by the teacher havenot yet referred to the Minister of Education regulation 22 of 2016 concerningprocess standards. Then based on the results of the analysis description refers toPermendikbud No. 22 of 2016 on the design of RPP that is in accordance with theCore Competencies, Basic Competencies, Learning Media, and Learning Stepssections.Keywords: description, implementation plan, thematic learning.